Synthetic viruses: a new opportunity to understand and prevent viral disease - Wimmer, Eckard; Mueller, Steffen; Tumpey, Terrence M; Taubenberger, Jeffery K (Nature biotechnology, 2009)
Rapid progress in DNA synthesis and sequencing is spearheading the deliberate, large-scale genetic alteration of organisms. These new advances in DNA manipulation have been extended to the level of whole-genome synthesis, as evident from the synthesis of poliovirus, from the resurrection of the extinct 1918 strain of influenza virus and of human endogenous retroviruses and from the restructuring of the phage T7 genome. The largest DNA synthesized so far is the 582,970 base pair genome of Mycoplasma genitalium , although, as yet, this synthetic DNA has not been 'booted' to life. As genome synthesis is independent of a natural template, it allows modification of the structure and function of a virus's genetic information to an extent that was hitherto impossible. The common goal of this new strategy is to further our understanding of an organism's properties, particularly its pathogenic armory if it causes disease in humans, and to make use of this new information to protect from, or treat, human viral disease. Although only a few applications of virus synthesis have been described as yet, key recent findings have been the resurrection of the 1918 influenza virus and the generation of codon- and codon pair–deoptimized polioviruses.